WHO Hand Hygiene Observation Form for Application in an Optometric Training Facility in a Tertiary Eye Care Hospital in Punjab, Pakistan. - Sehar, Nisma; Asgher, Mehmona; Batool, Isra; Ayuub, Fareeha; Saeed, Amber (Optometry & Visual Performance, 2024)
Background: Adherence to hand hygiene practices is essential in healthcare settings for the safety of both patients and health professionals. This study assesses the application and knowledge of hand hygiene practices among students of optometry. Methods: A cross-sectional study was conducted on 69 students of all four professional years of optometry. Data was collected with a universal non-probability sampling technique by using an adapted World Health Organization (WHO) Hand-Hygiene Knowledge questionnaire for health-care workers along with a WHO Observation form. Results: Fifty-eight students completed the adapted WHO Observation form, according to which most of the instruments were not disinfected before use. The adapted WHO Hand-Hygiene Knowledge questionnaire was filled out by all students. Fifty-four (78.2%) students did not use an alcohol hand rub routinely. Only 15 (21.7%) students had received training in hand hygiene in the last three years, and 27 (39.1%) were aware of "My Five Moments for Hand Hygiene." Forty-two (60.9%) students washed their hands 10 times a day, while 33 (47.8%) students stated that an alcohol hand rub requires 20 seconds to kill most of the germs. No statistically significant differences between students of all professional years and timings recommended by WHO were observed (p=0.370). According to 57 (82.6%) students, practicing hand hygiene actions before touching a patient can reduce the transfer of germs to patients with no significant differences found between students, professional years, and hand hygiene knowledge (p=0.885). Conclusions: Regulations governing hand hygiene, including the use of alcohol rubs, were not consistently enforced in the practices assessed. The majority of the students was unaware of the five moments of hand hygiene and had not undergone any formal hygiene training.